Processos de desfluoretação de águas subterrâneas a partir do uso de coagulantes naturais e do processo de separação por membranas - Bazanella, Gisele Cristina dos Santos (2010)
The occurrence of excess fluoride in groundwater is very concerning and has become more and more frequent in many countries. This is due to a general and important characteristic of water: It dissolves almost all substances and consequently contains gases and minerals from the air and soil in solution. However, the expansion of anthropic activities has led to the pollution of aquifers, contributing to the increase in toxic compounds, such as fluoride. The consumption of water with high levels of fluoride can result in dental and skeletal fluorosis, which is a chronic fluorine poisoning that promotes changes in teeth and / or bones. The fluoride levels established as optimal in drinking water vary from 0.7 to 1.5 mg F-/ L, according to annual average temperatures. Therefore, the objective of this work was to verify the efficiency of fluoride removal from groundwater that presented excess of it. Three different treatments were studied: use of natural coagulants (Moringa oleifera, chitosan and tanfloc), membrane separation process, and combined treatment - coagulation with Moringa oleifera seed extract followed by membrane separation process. The coagulation assays were performed in "jar-test". Moringa oleifera was used in the form of extract in different concentrations (5, 10, 25, and 50 g/L). Chitosan and tanfloc were commercial products, diluted to the desired concentrations (10% and 50% and 5 g/L and 25 g/L, respectively). In the tests with membranes, different porosities (0.005 μm; 0.45 μm; 4 KDa and 5 KDa) and different operating conditions (pressures of 1, 2, 3, and 4 bar; temperatures of 25 and 36 oC) were used. The combined treatment consisted of subjecting the water with excess fluoride (10 mgF-/L), to a previous treatment with different Moringa oleifera seed extracts in different concentrations, followed by passage through the ultrafiltration module using different membranes and operating conditions. It is noteworthy that the fluoridated water used in the process simulated groundwater with excess fluoride problems. At the end of each process the water was analyzed for fluoride, color and turbidity. The results showed removal of up to 90.9% for treatment with Moringa oleifera seed extract and 89.33% for the combined process. The combined treatment was found to be an excellent alternative to water treatment when the fluoride concentration is above that permitted by law, as in this case the water comes out fully treated, which means that color and turbidity parameters are also within the permitted standards, which is not the case in the coagulation process.